PENGEMBANGAN PERMAINAN MONOPOLI UNTUK MENGENALKAN PERILAKU BULLYING PADA ANAK USIA DINI DI RA NURUL JADID KELAS 0B - Arini Inayatul Fajriyah; Harjito; Arri Handayani (Journal of Education Reseach and Evaluation, 2025)
Bullying is still a phenomenon that occurs in early childhood education environments. Based on the results of data analysis from the survey, it was found that 42.6% of children have experienced bullying in the form of teasing or unpleasant treatment from their peers. Based on this, the purpose of this study is to develop a monopoly game to introduce bullying behavior in early childhood. This study uses a Research and Development (R&D) approach with the Borg and Gall model. The subjects of this study were 2 learning material experts and 2 learning media experts. The trial subjects in this study were teachers and class students aged between 5 and 6 years. In the initial stage, 10 students participated in a limited trial. The main field trial involved 55 students. Data collection methods used observation, interviews, questionnaires, and documents. Data collection instruments were in the form of expert validation sheets, teacher questionnaires, child questionnaires, and observation sheets of children's behavior before and after playing. The techniques used to analyze the data were quantitative and qualitative analysis. The results of the study, namely the assessment carried out by learning material experts, averaged a percentage of 74.6% in the category of Eligible. The assessment from learning media experts obtained a percentage of 75.0% and was categorized as Feasible. The results of student and teacher responses showed a positive response to the product. It was concluded that the developed product was categorized as Feasible for use in research. The anti-bullying monopoly game can be implemented in early childhood learning as an educational medium with notes on minor revisions to improve the quality of the material and media display.